Pelaksanaan Pengadaan Tanah untuk Kepentingan Umum oleh PT. PLN (Persero) di Riak Danau Tapan Kabupaten Pesisir Selatan - Fahlevi, Fahlevi; Warman, Kurnia; Nurdin, Zefrizal (UNES Law Review, 2023)
Procurement for the construction of a 150 KV substation by PT. PLN (Persero) UIP Sumbagteng, which is in Nagari Riak Danau Tapan, Basa Ampek Balai Tapan District, Pesisir Selatan Regency. that the stipulation of land acquisition for the construction of the 150 KV substation took place in 2017 with a total area of ​​1.8 hectares with the holder of the communal land rights being a legitimate member of their clan but the attempt to relinquish their rights was a mistake because it was directed at a person who is not the owner of the rights over the land. The type of research in the preparation of this thesis is sociological juridical research. The results of this study are 1) Land Acquisition Process for the Construction of a 150 KV Substation in Nagari Siak Danau Tapan, Pesisir Selatan Regency, which consists of several stages, namely (a) The planning stage which contains the aims and objectives of the development plan, Compliance with the Regional Spatial Plan (RTRW) ), and National and Regional Development Plans, Land layout includes administrative areas such as name of village, kelurahan, sub-district, province, Required land area, General description of land status, Estimated time for land acquisition implementation, Estimated timeframe for construction implementation, Estimated land value, (b) the Preparation Stage which includes notification of Development Planning, Dissemination in the form of face-to-face meetings, Letters of notification, Initial data collection of development plan locations, Determination of Development Locations, and (c) Implementation Phase which includes Inventory and Identification, Determination of Appraisers. Deliberation on determining compensation, granting compensation. In carrying out land acquisition for the purposes of building a 150 KVA substation in Nagari Riak Danau Tapan by PT. PLN (Persero) in the process of land acquisition and payment of compensation has made a mistake, which is a personal error (error in persona) because the person conducting the negotiations and dealings is the person who is only cultivating the land and is not the real owner of the rights. 2) Legal Consequences Arising from the Land Acquisition Process for Public Interests that Does Not Use the Deed of Relinquishment of Rights, namely: legal defects due to the statement of Relinquishment of Rights made before a Notary is more accountable both formally and materially even though the law allows for other ways other than the existence notary deed regarding the release of rights. Thus the fulfilment of the Theory of Responsibility that the researcher uses in this thesis is not fulfilled, because apart from not being able to account for the authenticity of the statement of waiver of rights from the owner of the right, in the process of completing documents the statement made underhand is also vulnerable to falsification and this is a crime.